From Tradition to Transformation: Evolving Gender Norms in Contemporary Africa - Tamunomiegbam, Alex; Arinze, David (American Journal of Public Policy and Administration, 2024)
Purpose: The study aims to explore the evolution of gender norms in contemporary Africa, examining the shift from traditional roles to transformative gender identities and relations. Materials and Methods: Anchored on Social Constructionist theory, this study employs a qualitative research design to investigate into the nuances of evolving gender norms. Through content analysis of various texts, narratives, and media, the research investigates how gender norms are constructed, challenged, and reshaped within the African context. Findings: The findings reveal a complex interplay between traditional values and emerging gender perspectives, influenced by factors such as globalization, education, and activism. While progress is evident, persistent gender biases and inequalities highlight the incomplete nature of this transformation. The conclusion underscores the fluidity of gender norms and the potential for further evolution towards gender equity. Implications to Theory, Practice and Policy: This study holds significant implications to scholarship, as its outcomes and suggestions aim to refine the social constructivist theory, which underpins the analysis, and to enhance policymaking to promote women's rights in African societies. Additionally, it boosts initiatives that confront enduring patriarchal standards by incorporating gender education into academic curricula, encouraging public conversations about gender equality, and backing grassroots campaigns that push for transformative gender norms. These measures are pivotal in accelerating the progress towards a more inclusive and equitable future for all Africans.